Transesophageal Echocardiography–Derived Renal Resistive Index after Cardiopulmonary Bypass: A Novel Hemodynamic Marker of Postoperative Renal Vulnerability - Parna, Dian Raseka; Kurniawaty, Juni (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Acute kidney injury (AKI) remains a frequent and clinically significant complication following cardiopulmonary bypass (CPB), often developing despite apparently stable systemic hemodynamics. Conventional renal monitoring relies on delayed biochemical markers that fail to capture early disturbances in renal microcirculation. The renal resistive index (RRI) has emerged as a dynamic indicator of renal vascular resistance and microcirculatory stress, but its perioperative application has been limited by the practicality of transabdominal ultrasonography. Transesophageal echocardiography (TEE), routinely used during cardiac surgery, offers a unique opportunity for real-time assessment of renal hemodynamics during and immediately after CPB. This literature review synthesizes current evidence on the feasibility, physiological basis, and clinical relevance of TEE-derived RRI measurement in the post-CPB setting. The reviewed studies suggest that elevated RRI values reflect a complex interaction of renal vascular resistance, venous congestion, altered pulsatility, and inflammatory endothelial dysfunction rather than isolated reductions in renal blood flow. Importantly, RRI elevation frequently precedes changes in serum creatinine or urine output and has been associated with an increased risk of postoperative renal dysfunction, even in patients without overt hypotension or low cardiac output. TEE-derived RRI therefore represents a promising, underutilized hemodynamic marker for early identification of postoperative renal vulnerability and may support more proactive, organ-protective hemodynamic management strategies following cardiopulmonary bypass